Reconstruction through the Use of the Posterior Peroneum for Coverage of Defects of the Distal Third of the Leg - Erazo, Esteban Wilfredo Vivas; Walles, Jonathan González; Bejarano, Harry Acosta; Ustariz, Rodolfo José Marquez; Mejía, Antonio Ortega; Escobar, Pastor Leonardo Jurado; Cabra, Oswaldo Pérez; Rodriguez, Ana Cristina Eraso (Jour Med Resh and Health Sci, 2022)
The lower limb has objectives such as support, stability and power that allows the human being mobility and ability to perform different movements. The fibula and tibia, being the bones that make up the lower limb, can present injuries or wounds that prevent these actions, whether due to accidents, trauma, ulcers, injuries secondary to fractures, therefore, the use of flaps has been considered an alternative in lower limb reconstruction. The posterior fibular flap, given its anatomical characteristics, irrigates a larger area, which allows it to be widely used in the reconstruction of defects in the distal third of the leg, especially in the ankle and heel. Therefore, in the following review article we focus on the application of the posterior fibular flap in the coverage of the distal third of the leg and its usefulness for the reconstruction of said wounds.